Pengaruh Kompetensi Aparatur Pemerintah Desa, Pelatihan Pengguna, Dan Gaya Kepemimpinan Terhadap Kualitas Implementasi Sistem Keuangan Desa - Made Putri Irayani; Made Aristia Prayudi (Universitas Pendidikan Ganesha, 2022)
This study aims to determine the effect of village government apparatus competence, user training, and leadership style on the quality of village financial system implementation in Buleleng Regency. The research method used in this study is a quantitative method with primary data obtained from questionnaires and measured using a Likert scale. The population of this research is the village secretary, finance officer, and village operator staff. The sample in this study amounted to 291 respondents who were selected using proportional random sampling technique. The data analysis method used in this study is a multiple linear analysis method with the help of SPSS version 24. The results show that the competency variable of the village government apparatus (X1) has a positive and significant effect on the quality of siskeudes implementation, the user training variable (X2) has a positive and significant effect. on the quality ofimplementation siskeudes, and the leadership style variable (X3) has a positive and significant effect on the quality of siskeudes implementation.